2015
DOI: 10.1021/acs.jpcc.5b04042
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Phase Transition in Photosensitive Liposomes by Advanced QCM

Abstract: In this work an impedance-based quartz crystal microbalance (QCM) is used to detect heat induced changes in the viscoelastic properties in the films of adsorbed liposomes. Liposomes are bound to a polymer-modified QCM surface, and heat is induced in the bilayer via light absorption into gold nanoparticles (GNPs) embedded in the liposomes. Due to very rapid heat transfer at the nanoscale, nanoparticles can reside either in the liposome cavity or within the bilayer to cause changes in the lipid viscoelasticity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Several studies have reported similar observations, describing lipid bilayers that underwent phase transition by CW laser in the presence of gold nanorods and released drug. This study differs from the previous study in two-fold: (1) we demonstrated the lipid bilayer phase transition by pulsed laser and (2) further verified reversibility of individual liposomes via collision frequency measurement.…”
Section: Resultssupporting
confidence: 55%
“…Several studies have reported similar observations, describing lipid bilayers that underwent phase transition by CW laser in the presence of gold nanorods and released drug. This study differs from the previous study in two-fold: (1) we demonstrated the lipid bilayer phase transition by pulsed laser and (2) further verified reversibility of individual liposomes via collision frequency measurement.…”
Section: Resultssupporting
confidence: 55%
“…4,5,8,14 Gold nanoparticles convert absorbed light energy to heat, permeabilizing the liposomal membrane and enabling drug release to the surrounding tissue. 4,5,15,16 The maximum absorption wavelength of the gold nanoparticles depends on the size and shape of the particles. 17−19 Small gold nanoparticles absorb light in the ultraviolet range (<400 nm), but such short wavelengths penetrate tissues poorly and may cause DNA damage to the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes are nanocarriers that are already in clinical use; they are biocompatible, and their surface and lipid wall properties can be modified in a versatile manner . Previously, light-activated release from liposomes has been achieved using gold nanoparticles as a light-triggering component. ,,, Gold nanoparticles convert absorbed light energy to heat, permeabilizing the liposomal membrane and enabling drug release to the surrounding tissue. ,,, The maximum absorption wavelength of the gold nanoparticles depends on the size and shape of the particles. Small gold nanoparticles absorb light in the ultraviolet range (<400 nm), but such short wavelengths penetrate tissues poorly and may cause DNA damage to the cells. Larger gold nanoparticles absorb light in the near IR range (700–900 nm), , the “phototherapeutic window”. These wavelengths are safer to the tissues and show maximal tissue penetration. , Therefore, the use of near IR light is a promising approach for light-triggered drug delivery and phototherapy. , …”
Section: Introductionmentioning
confidence: 99%
“…6,11 As the GNP turns absorbed light energy into heat, heat is transported to the surrounding lipid bilayer (MD simulation; see e.g. ref 12) and the lipids undergo a phase transition 8,13 followed by drug release. 6,9 The underlying mechanism of action is no different than in thermotherapy, where GNPs are heated by light in order to kill cancer cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Light-to-heat conversion has been done by encapsulating hydrophilic gold nanoparticles (GNPs) inside the liposomes or hydrophobic GNPs into the bilayer of the liposomes. , As the GNP turns absorbed light energy into heat, heat is transported to the surrounding lipid bilayer (MD simulation; see e.g. ref ) and the lipids undergo a phase transition , followed by drug release. , The underlying mechanism of action is no different than in thermotherapy, where GNPs are heated by light in order to kill cancer cells . In addition to gold colloids, some organic dyes such as indocyanine green (ICG) and IR820 act as a photothermal agent and can also be used in thermal therapy. , Remarkably, these dyes have so far not been used in drug release from liposomes.…”
Section: Introductionmentioning
confidence: 99%